Factor de riesgo suicida según dos cuestionarios, y factores asociados en estudiantes de la universidad nacional de Colombia sede Manizales (2015)
Objective: to determine suicide risk and other related factors according to two surveys conducted at the Universidad Nacional de Colombia of Manizales (Caldas, Manizales). Materials and Methods: cross-sectional design with 255 students of 3 programs of the Universidad Nacional. Results: prevalence of suicide tendency according to Plutchik: 6,7 %; according to Beck: 19,7 %. Good family functioning: 39,8 %; absent depression: 55,7 %. A significant correlation was found between suicide risk factor (Plutchnik) and gender, metal musical, exercise, depression, and family functioning. According to Beck, these factors are metal musical gender, depression and family functioning. Conclusions: The prevalence of suicide risk in this population is below the average when compared to other research.